Vibrotactile Perception for Sensorimotor Augmentation: Perceptual Discrimination of Vibrotactile Stimuli Induced by Low-Cost Eccentric Rotating Mass Motors at Different Body Locations in Young, Middle-Aged, and Older Adults - Ella Pomplun; Ashiya Thomas; Erin Corrigan; Valay A. Shah; Valay A. Shah; Leigh A. Mrotek; Robert A. Scheidt (Frontiers in Rehabilitation Sciences, 2022)
Sensory augmentation technologies are being developed to convey useful supplemental sensory cues to people in comfortable, unobtrusive ways for the purpose of improving the ongoing control of volitional movement. Low-cost vibration motors are strong contenders for providing supplemental cues intended to enhance or augment closed-loop feedback control of limb movements in patients with proprioceptive deficits, but who still retain the ability to generate movement. However, it remains unclear what form such cues should take and where on the body they may be applied to enhance the perception-cognition-action cycle implicit in closed-loop feedback control. As a step toward addressing this knowledge gap, we used low-cost, wearable technology to examine the perceptual acuity of vibrotactile stimulus intensity discrimination at several candidate sites on the body in a sample of participants spanning a wide age range. We also sought to determine the extent to which the acuity of vibrotactile discrimination can improve over several days of discrimination training. Healthy adults performed a series of 2-alternative forced choice experiments that quantified capability to perceive small differences in the intensity of stimuli provided by low-cost eccentric rotating mass vibration motors fixed at various body locations. In one set of experiments, we found that the acuity of intensity discrimination was poorer in older participants than in middle-aged and younger participants, and that stimuli applied to the torso were systematically harder to discriminate than stimuli applied to the forearm, knee, or shoulders, which all had similar acuities. In another set of experiments, we found that older adults could improve intensity discrimination over the course of 3 days of practice on that task such that their final performance did not differ significantly from that of younger adults. These findings may be useful for future development of wearable technologies intended to improve the control of movements through the application of supplemental vibrotactile cues.